(untitled) (The Review of Diabetic Studies, 2025)
Background:​‍​‌‍​‍‌​‍​‌‍​‍‌ The volume of orthodontic patient trends has been so significant that band researchers have been quite heavily worried about it. Consequently, those patients with periodontal diseases have become the major number of the band patients, thus it has been very important what the treatment outcomes will be in the far future. The objective of this systematic review and meta-analysis was to assess treatment stability and long-term periodontal health in adult patients with periodontal disease after orthodontic therapy. Methods: For pertinent studies published between 2000 and 2025, a thorough literature search was carried out in PubMed, Web of Science, and Scopus. Only prospective clinical studies and randomized controlled trials (RCTs) that reported orthodontic treatment outcomes in patients with periodontal disease and had a minimum 12-month follow-up were considered. Clinical attachment level (CAL), probing pocket depth (PPD), bleeding on probing (BOP), alveolar bone level (ABL), and treatment stability were the main outcomes evaluated. Random-effects models were used for meta-analyses. Results: analysis included ten studies comprising 446 patients. The findings demonstrate that integrated periodontal-orthodontic therapy resulted in significantly better periodontal outcomes compared to periodontal treatment alone. The meta-analyses showed significant improvements in key clinical parameters and enhanced treatment stability. This synthesis indicates that a combined approach is effective for achieving long-term periodontal health and stable orthodontic results in this patient population.mean CAL gains of 0.86 mm (95% CI: 0.72-1.00), PPD reductions of 0.91 mm (95% CI: 0.77-1.05), and ABL improvements of 0.42 mm (95% CI: 0.31-0.53). Stability was good with retention and a slight relapse (8-15%) at 12-60 months. The therapeutic effect was significantly stronger in the combined treatment groups (93.75% vs. 75.00%, p < 0.05). Conclusions: If periodontal stabilization has been achieved, orthodontic treatment of adult patients is not a cause that it damages the periodontium and, in fact, may be the source of some of the extra benefits that are possible to be achieved by periodontal treatment alone. With the correct treatment planning, regular periodontal maintenance, and extended retention protocols, long-term stability can be achieved.